Taekwondo: Physiological responses and match analysis - Matsushigue, K. A.; Hartmann, K.; Franchini, E. (The Journal of Strength and Conditioning Research, 2009)
The aim of the present study was to determine the time structure and physiological responses during Songahm Taekwondo (TKD) competition and to compare these variables between winner and non-winner athletes. Fourteen men subjects were analyzed. Blood lactate concentration (LA) and heart rate (HR) were determined before and after the match. The match was filmed for the determination of the number of techniques used, the duration of effort and rest periods (RPs), and the interval between high-intensity movements (HM). Post-match LA was 7.5 +/- 3.8 mmol[middle dot]L-1, HR was 183 +/- 9 b[middle dot]min-1, and HM was 31 +/- 16 seconds. The mean effort time (8 +/- 2 seconds) did not differ from mean interval time (8 +/- 3 seconds). Winners used a smaller total number of techniques, but post-match LA or HR did not differ from that of non-winners. In conclusion, the glycolytic metabolism was not the predominant energy source and the physiological responses did not differ between winners and non-winners. Coaches and sports scientists should prepare a technical or physical training session considering the low glycolytic contribution in this sport, hence the training protocol should involve high-intensity movements interspersed with longer RPs to provide the creatine phosphate recovery, with special attention given to the technical quality of TKD skills and not to higher technique volume during a simulation of matches.